A new TPE-based tetrapodal ligand and its Ln(iii) complexes: multi-stimuli responsive AIE (aggregation-induced emission)/ILCT(intraligand charge transfer)-bifunctional photoluminescence and NIR emission sensitization. Issue 3 (8th December 2015) - Zhu, Yi-Xuan; Wei, Zhang-Wen; Pan, Mei; Wang, Hai-Ping; Zhang, Jian-Yong; Su, Cheng-Yong
Abstract : AIE and ILCT properties are combined in one zwitterionic-type ligand and its assembled lanthanide complexes. Abstract : A tetrapodal zwitterionic-type ligand featuring both AIE (aggregation-induced emission) and ILCT (intraligand charge transfer) properties, namely 1, 1′, 1′′, 1′′′-(4, 4′, 4′′, 4′′′-(ethene-1, 1, 2, 2-tetrayl)tetrakis(benzene-4, 1-diyl))tetrakis(methylene)tetrapyridin-4(1 H )-one (TPE-4PO) has been designed and applied to the assembly of lanthanide complexes LIFM-21(Ln) (Ln = Sm, Eu, Gd, Tb and Dy). Apart from sensitization of NIR emission of Sm 3+ and Dy 3+, the resulting ligand and lanthanide complexes show both AIE and ILCT-related photoluminescence behaviors. The photo-response of this system to different aggregation states, solvents' polarity and mechanical grinding was demonstrated by distinguishable emission intensities and colours.